The Effect Of Promotion, Price, And Quality Of Service On Customer Satisfaction Of PT. Aseng Keto Sukses Medan - Ricky Rafii Ritonga; Christian Ardy; Felix Giovanni Chandra; Nicholas Geral Cendana; Egon Sius Purba (International Journal of Science, Technology & Management, 2022)
This research was motivated by a decrease in the number of customers of PT. Aseng Ketok Successful in 2020. The decrease in the number of customers indicates that the satisfaction of pt. Aseng Ketok Success Medan. By looking at the problems that exist, this research is directed to analyze how to increase satisfaction by supporting increased promotion, price, and, quality of service. In this study used is the criteria of permanent customers, which are meant by permanent customers here are service users who have more than twice used the services of PT. Aseng Ketok Success. The number of samples is determined based on calculations of the Slovin formula with a tolerable error rate of 5%, then the sample count will be obtained as many as 150 people. The data analysis method used in this study is Multiple Regression, were previously tested the validity, reliability, and classical assumptions. The results showed that promotion, price, and quality of service have a positive and significant influence on customer satisfaction. The author's advice is to increase customer satisfaction can be done by improving promotions, maintaining customer satisfaction, and pricing more in line with customer capabilities. PT. Aseng Ketok Sukses Medan needs to maintain elements that have been considered good by customers and need to improve things that are still lacking.